Foreign company misconduct and how consumers' punitive intent is influenced by country stereotypes and the perceived similarity between the foreign country and the home country. Issue 5 (October 2022) - Barbarossa, Camilla; Buzeta, Cristian; De Pelsmacker, Patrick; Moons, Ingrid
Abstract: Using a previously untested similarity contingency model of country stereotypes, this study assesses the effects of country stereotypes, perceived country similarity, and their interplay on emotion-driven punitive intent toward foreign, wrongdoing companies. In Study 1, positive country stereotypes (warmth, competence) mitigate punitive intent by diminishing agonistic emotions (contempt, anger, and disgust). Study 2 demonstrates that perceived similarity with a wrongdoing company's country of origin moderates the indirect effects of country stereotypes on emotion-driven punitive intent. Compensatory effects between country stereotypes and perceived country similarity emerge; with greater (lower) perceived country similarity, the indirect effects of country stereotypes on emotion-driven punitive intent are weaker (stronger). The results provide companies with relevant insights into (1) why consumers emotionally react as they do to wrongdoing companies of different nationalities and (2) how to counterbalance negative effects of company misconduct by harmonizing elements of countries' warmth, competence, and perceived country similarity in branding and communication content. Highlights: Consumers' punitive intent toward foreign company misconduct is influenced by country stereotypes. Agonistic emotions mediate the effects of country stereotypes on punitive intent. The perceived similarity between the foreign country and the home country moderates the country stereotypes effects. Compensatory effects of country stereotypes and the perceived country similarity emerge. The compensatory effects are stable across different levels of consumers' cosmopolitanism.